Correction: Division time-based amplifiers for stochastic gene expression. Issue 2 (12th January 2016) - Wang, Haohua; Yuan, Zhanjiang; Liu, Peijiang; Zhou, Tianshou
Abstract : Correction for 'Division time-based amplifiers for stochastic gene expression' by Haohua Wang et al., Mol. BioSyst., 2015, 11, 2417–2428.